Gene Flow Patterns among Aedes aegypti (Diptera: Culicidae) Populations in Sri Lanka - Fernando, H.S.D; Hapugoda, M; Perera, R; Black IV, W. C; De Silva, B. G. D. N. K. (Insects, 2020)
In Sri Lanka, dengue is the most serious arboviral disease. Recent increases in dengue cases suggest a higher infection rate and spread of the disease to new areas. The present study exploresgeneﬂowpatternsofAe. aegypti,themainvectorofdenguedisease,among10collectionsites includingmajorportsandinlandcitiesusingvariationsat11microsatelliteloci. Discriminantanalysis of principal components (DAPC) and k-means clustering estimated eight genetic clusters. Analysis of Molecular Variance (AMOVA) estimated equal variances among cities and among collections in Colombo, Sri Lanka. Signiﬁcant evidence, although weak, was detected for isolation by distance. Analysis of gene ﬂow rates and directions using MIGRATE-n indicated that populations throughout the island served as a source of immigrants for Colombo with abundant gene ﬂow among major commercialcitiesinSriLanka,whichappeartoreceivemigrantmosquitoesfromthroughoutSriLanka. The observed patterns probably arise through human movement of Ae. aegypti during commerce fromthroughoutSriLankaintoColomboincreasingtheriskofspread. Thepatternsuncoveredinthis studyaresigniﬁcantforglobalhealthasSriLankaissituatedalongakeyinternationalshippingroute.
Keywords: Aedes aegypti; population structure; gene ﬂow patterns; Sri Lanka